Pengaruh Kepemilikan Institusional, KepemilikanManajerial, Profitabilitas, Dan Ukuran PerusahaanTerhadap Kebijakan Hutang Pada Perusahaan lq45 yangTerdaftar Di Bei Tahun 2010-2014 - Andriyono, Eko (2016)
his research aimed to analyze the influence of Institutional Ownership, Managerial Ownership, Profitability, and Firm Size to Debt Ratio in LQ45 companies which listed in Indonesian Stock Exchange (IDX) from 2010 to 2014. The research sample consisted of 6 companies of 45 LQ45 companies listed on IDX by the observation numbers of 30 observational data. The sampling method was done by using purposive sampling. The researched data was obtained from ICMD. The data analysis technique used in this research is multiple linear regression. Hypothesis testing using t statistics used in this research to test the partial regression coefficients as well as f-statistics to test the significance of the influence together, with the level of significance of 5%. Other than that, all the variables had been tested with the Normality test, Multicollinearity test, Autocorrelation test, and Heteroskidastity test. The results showed that all variables passed the classical assumption test and suitable to be used as research data. T-test statistical on Debt Ratio indicated that Profitability and Firm Size has significant influence on Debt Ratio, whereas Institution Ownership, and Managerial Ownership has no significant influence on Debt Ratio.